THE ROLE OF PERCEIVED PRODUCT ATTRIBUTES AND BRAND AWARENESS IN CREATING CONSUMER PURCHASE INTENTION ON LOCAL FASHION BRAND (Empirical Study on Potential Consumer of Screamous Clothing-Retail Company, Malang) - Tri Ariyani; Dodi Wirawan Irawanto (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This study aims to examine and explain the role of perceived product attributes and brand awareness in creating consumer purchase intention on local fashion brand in Indonesia. The research was conducted in the area of Malang City. Further purposive sampling technique was used in this research with 120 respondents. The analysis tools are Multiple Linear Regression Analysis to determine the relationship between independent variable and dependent variable. The result of the study explained that there is a significant effect between perceived product attributes to the consumer purchase intention and brand awareness to consumer purchase intention both partially and simultaneously. Therefore, the research result shows that brand awareness is the dominant variable that affects consumer purchase intention.Keywords: Perceived Product Attributes, Brand Awareness, Purchase Intention